MYOPIA: MODERN METHODS OF TREATMENT - Kholmatova Yokutkhon Nematillaevna (Modern American Journals, 2026)
Myopia, which is widely known as a nearsightedness, is a condition that affects millions of people worldwide and is expected to reach almost half of the total population by 2050, according to the forecasts. Research results suggest that low-dose atropine is very effective in retarding the progression of myopia, and besides it, orthokeratology and peripheral defocus lenses are also good options for children. On the other hand, surgical procedures such as LASIK and the insertion of collamer lenses can achieve the complete correction of myopia in adults with stable refractive error.
Keywords: Myopia, refractive error, atropine therapy, orthokeratology, LASIK, myopia control, progressive myopia, optical correction